A review of successful flavivirus vaccines and the problems with those flaviviruses for which vaccines are not yet available - Tomohiro Ishikawa (2018)
Genus flavivirus comprises many important human pathogens causing public health problems worldwide. Some flavivirus infections are characterized by a relatively high mortality rate and/or high sequelae rate in survivors. Because most flavivirus life cycles are maintained between arthropod vectors and amplifying/reservoir hosts in the absence of humans, eradication of flaviviruses might be extremely difficult. Flavivirus vaccine development is considered a reasonable method to prevent flavivirus infections. Some vaccines have been successfully developed, but others have not, regardless of much effort. This review article describes currently available flavivirus vaccines against yellow fever, Japanese encephalitis, and tick-borne encephalitis. In addition, the current status of dengue and West Nile virus vaccine development is reviewed and problems regarding their development are discussed. © 2014 Elsevier Ltd.